MNCs and their Role in the Economies of CEE. The Bulgarian Case - Ivona Yakimova; Tamara Todorova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
After nearly a decade of profound economic changes and a market transformation the countries in Central and Eastern Europe now face the challenge of development and sustainable growth. The development priorities include achieving a high income growth for their economies by raising investment rates, strengthening technological capacities and skills, and improving the competitiveness of their exports, distributing the benefits of growth equitably by creating more and better employment opportunities. An important factor for reaching these goals is not only the input and national endowments of the country but also the world economic environment and the main economic participants in it as for most of the transition countries (the smaller ones, in particular) the exogenous impetus turns to be the main determinant for the success of the reforms. The reason behind it is the full exhaustion of the ineffective usage of the national resources (natural, human, capital, financial) in the old "socialist" model and the great economic and technology gap which has existed between the region and the rest of the developed economic world. The purpose of the paper is to reveal the importance of MNCs activities in Central and Eastern Europe for marketization of the region and for effective integration in the globalizing world economy. The different aspects of MNCs' impact on Bulgarian economy are examined with respect to their new comparative advantages. The main determinants of the investment climate in the country are also studied and the special accent is put on commenting the results of an empirical study of MNCs transaction costs activities in Bulgaria and the critical issues concerning a better investment climate in the country. The last section of the paper deals with some conclusions and recommendations for more effective governmental policies towards MNCs as they are looked as "economic locomotives" of Bulgarian economy's sustainable growth.
Keywords: F23; O43; 330; Multinational corporations; Sustainable Growth